UMKM Cakap Digital melalui Penerapan E-Commerce: Studi Empiris di Kota Tarakan - Meylin Rahmawati; Sulistya Rini Pratiwi; Rika Wahyuni; Kartini, Kartini; Istianah Asas (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Measuring the effectiveness of e-commerce implementation is important to ensure online strategies meet MSME business goals. It helps evaluate whether investments in e-commerce are producing expected results, identify areas that need improvement, and adjust marketing approaches to increase sales and customer satisfaction. Effective measurement enables MSMEs to make data-driven decisions, maximize resources and strengthen their competitive position in the digital market. Based on this, this study aims to identify the benefits and barriers and measure effectiveness in implementing e-commerce. The method used in this research is effectiveness and a mix methods approach regarding barriers and benefits. The results show that the most perceived benefit is being able to expand the market, with the highest obstacle being low understanding of technology. The effectiveness ratio of implementing e-commerce in Tarakan City is 73%, which is in the quite effective category. Meanwhile, government support for the implementation of e-commerce by MSMEs is in the ineffective category.